Recycling of ABS operating elements obtained from industry 3D printing machines - Marciniak, Dawid; Czyżewski, Piotr; Sykutera, Dariusz; Bieliński, Marek (Polimery, 2021)
The article presents new application of the material obtained from the recycling of acrylonitrilebutadiene-styrene (ABS) – the material acquired from operating parts of industry Dimension Elite 3D printer by Stratasys. The operating parts were used to prepare the regranulate and to produce filament, the latter of which was applied used in the FFF technology (Fused Filament Fabrication). Manufactured in the FFF technology, test specimens were used to determine the selected mechanical properties and to compare the obtained results with the properties characteristic of molded pieces made of ABS regranulate that were produced by injection molding. The paper presents results of tests performed on a filament, obtained from the ABS regranulate and indicates characteristic processing properties of that material. It also discusses beneficial processing parameters for injection molding (IM) and 3D printing (FFF). The study also presents selected results of tests of functional properties of ABS products in the FFF technology. The research results have allowed to assess the possibility of recycling of the operating parts of 3D printers in FFF.